Importance of Environmental Education in Socio-Natural Risk Management in Five Countries of Latin America and the Caribbean - Martha Melizza Ordóñez-Díaz; Luisa María Montes-Arias; Giovanna del Pilar Garzón-Cortes (Universidad Nacional, Costa Rica, 2017)
Considering environmental education as a social tool allowing individuals to achieve a significant knowledge of the inhabited environment, to reduce the probability of occurrence of a disaster, and to respond to the presence of natural phenomena to which people are vulnerable, this article aims to generate a space for reflection on the importance of environmental education in the management of the social and natural risk in five countries of Latin America and the Caribbean. For this purpose, the paper presents a descriptive review of primary and secondary bibliographical sources referring to the performance of the management of social and natural risks related to environmental education in Colombia, Nicaragua, Mexico, Chile, and Jamaica between 1994 and 2015. In this period, a solid administrative and legislative organization of this management and environmental education is evident, but these two themes are clearly separated when implementing citizen projects: a situation that has generated shortcomings in the management of natural disasters, specifically under the principles of precaution and prevention. For this reason, this article offers a series of recommendations that include the dissemination of information, the creation of centers for the management of risk reduction, the strengthening of communication strategies, and the establishment of response plans and post-disaster recovery.